Investigation into the influence of electrode material on the IEC Inclined Plane test procedure (IEC 60587) when applied for Direct Current (DC) voltages - Swinny, Raphael (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.